Achieving the International Benchmarks for Adult Literacy in Nigeria : Post 2015 Challenges and Prospects - Olojede, Adeshina Abideen (European Scientific Journal, ESJ, 2017)
The story of Adult education in Nigeria is not complete without the activities of itinerant Islamic scholars and traders dating as far back as the 14th century. The Methodist mission, the Church Missionary Society (C.M.S) and other Christian churches pioneered what can be termed as â€œmodern literacyâ€ in Nigeria. The major difference between the activities of Islamic missionaries and Christian missionaries is the acceptance of western education in the south and its rejection in the north. Despite this early involvement in literacy activities, illiteracy still persists in Nigeria. Literacy developments efforts in Nigeria include collaboration with UNESCO in the establishment of an Adult Literacy Institute in Ibadan. In 1965, the University of Ibadan started the training of professional adult educators. Other initiatives include pre-primary education, primary education, the first three years of secondary education (JSS), and literacy for adolescents, adults and womenâ€™s education. To help improve literacy development situation, the International Community on Education has put forward a 12 points benchmark on literacy delivery. With the current rate of illiteracy and the fact that the deadline of 2015 which was earlier scheduled for halving the illiterates population could not be met, the credibility of the government activities, most especially in the area of funding, commitment, programmes, strategies and the institutions established on the success or otherwise on the benchmarks as far as Nigeria is concerned has been called into question. Using relevant literature on the topic and personal experience of the researcher, this paper is written, to access Nigeriaâ€™s performance in the realization of these benchmarks. However, it established the problems and offers possible recommendations that if applied, would put the country on track again as post 2015 literacy development strategy.